2021
DOI: 10.1103/physrevlett.127.152701
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the C13(α,n)O

Abstract: nucleosynthesis yields up to the stellar surface, is called 13 the third dredge up. As early recognized, the creation 14 of a 13 C-pocket within the He-rich mantel, through the 15 reaction 12 C(p,γ) 13 N(β + ) 13 C, is a byproduct of these 16 recursive mixing episodes [2, 3]. Such a thin pocket (a 17 few 10 −5 M of 13 C) harbors one of the most important 18 nucleosynthesis sites in the Universe. During the period 19 between two TPs, the temperature attains about 90 MK 20 and 13 C is activated as a neutron sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…EMPIRE [77], and NON-SMOKER [8]. Figure 5 shows the MACS results of the present work for 33 S, 59 Ni, and 71 Ge target nuclei in comparison with those from several other model calculations based on different assumptions on the nuclear properties and approaches in modeling the reaction mechanism. These include NON-SMOKER reaction cross sections data base [8], Evaluated Nuclear Data File (ENDF) [7], Joint Evaluated Fission and Fusion (JEFF) Nuclear Data Library [9], JENDL Library for Nuclear Science and Engineering [10], ROSFOND nuclear data [11], and Chinese Evaluated Nuclear Data Library (CENDL) [12,13].…”
Section: B Astrophysically Relevant Neutron Energy Window For (N α) R...mentioning
confidence: 90%
See 3 more Smart Citations
“…EMPIRE [77], and NON-SMOKER [8]. Figure 5 shows the MACS results of the present work for 33 S, 59 Ni, and 71 Ge target nuclei in comparison with those from several other model calculations based on different assumptions on the nuclear properties and approaches in modeling the reaction mechanism. These include NON-SMOKER reaction cross sections data base [8], Evaluated Nuclear Data File (ENDF) [7], Joint Evaluated Fission and Fusion (JEFF) Nuclear Data Library [9], JENDL Library for Nuclear Science and Engineering [10], ROSFOND nuclear data [11], and Chinese Evaluated Nuclear Data Library (CENDL) [12,13].…”
Section: B Astrophysically Relevant Neutron Energy Window For (N α) R...mentioning
confidence: 90%
“…The theory framework outlined in Sec.II is employed in model calculations for a set of nuclei already introduced in s-process network calculations of a massive star, including convective He burning core and shell C-burning [30]. Figure 1 shows the (n, α) reaction cross sections for the following nuclei: 17 O, 18 F, 22 Na, 26 Al, 33 S, 37 Ar, 39 Ar, 40 K, 41 Ca, 59 Ni, 65 Zn, and 71 Ge. For the sake of completeness, we present not only astrophysically relevant low-energy range of the cross sections but a full result.…”
Section: A (N α) Reaction Cross Sections For S-process Nucleimentioning
confidence: 99%
See 2 more Smart Citations
“…The capability of FRUITY Magnetic models of matching grain data can be understood by focusing on the trends of 88 Sr and 138 Ba isotopes. Previous studies using post-processing s-process models found that 13 C pockets with a flat 13 C profile and masses larger than a few 10 −4 M are needed to explain the bulk of mainstream SiC grains with negative 88 Sr/ 86 Sr and 138 Ba/ 136 Ba isotope ratios [151]. The action of magnetic-buoyancy-mixing results in deep penetration of a few protons, so that, when H-burning restarts, almost all the protons are captured by 12 C, producing 13 C but a small amount of 14 N. Therefore, the ensuing 13 C pocket is quite extended and with a low and rather constant 13 C abundance (see Figure 2), as required to explain Sr-Ba grain data [144,164,165].…”
Section: Sic Grainsmentioning
confidence: 99%